Teaching power yoga for sports - Lawrence, Gwen (Champaign, IL Human Kinetics, 2019)
Show your athletes how power yoga can propel their performance to the next level. Teaching Power Yoga for Sports prepares you to develop and teach yoga programs that are directly relatable to specific sports and player positions, resulting in more resilient athletes who constantly compete at the top of their game
Why athletes need power yoga for sports -- Anatomy, alignment, and assessment -- Mindfulness tools -- Maximize your yoga practice -- Standing poses -- Seated poses -- Floor poses and inversions -- Sport-specific sequences -- Ready-to-use yoga sequences -- Restorative sequences
"Foreword by Tim Coughlin" -- book cover
Includes bibliographical references
Keywords: Hatha yoga; Athletes -- Training of